Hindī sāhitya ko Datta Dvijendra kī dena : Bhāratendottara Hindī sāhitya ke eka pramukha racanākāra kā jīvana tathā sāhitya : Datta Dvijendra granthāvalī - Datta Dvijendra, 1871-1909 (Rājyaśrī Prakāśana, 1978)
Includes a detailed introduction to the life and works of the author by the editor.